Reactivation Of Ion Exchange Resins For Water Treatment Application - Lai, Kher Wei (Universiti Sains Malaysia, 2022)
Ion exchange resin or IX resin is a synthetic polymeric ion exchanger that has been extensively used in water purification process to remove soluble ionized contaminant in water such as hardness ions (E.g., Ca, Mg). In water purification process, SAC (H-form) and SBA (OH-form) IX resins are commonly used. After several service cycle, the IX resins become spent and need to be regenerated so that is can be reused in the next service cycle. Several problems encountered during resins regeneration, which are resin fouling, low regeneration efficiency and high chemical consumption. The purpose of this research is to improve the resin regeneration process. To achieve the goal, the project has developed a brining process with optimized parameters for IX resin regeneration, as well as characterized properties and compare the water purification performance of the untreated IX resin and the pre-treated IX resin by demineralization process. Sodium chloride (NaCl) is selected to use as brining regenerant and the effect brining parameters are tested using batch method. This project shows that optimization of brining process is achieved by brining process in dried state with 5% brine solution and volumetric ratio of 1:1 at brining temperature of 55℃. From the result, brining is able to remove some impurities on the spent resins, increase the regeneration efficiency by partially remove hardness prior to regeneration and reduce chemical consumption by improving hardness removal capacity of low concentration regenerant (4% HCl). In demineralization, regeneration without brining will produce water with higher purity but regeneration with brining provide longer service life of resins.